Local Government Policies in Spatial Planning: Towards Sustainable Development in Indonesia - Elvira Hilwa Salsabila (CV. GovPlan Indonesia, 2025)
Spatial planning is an important instrument in realizing sustainable development at the regional level. Local government policies in spatial planning aim to regulate the use of space effectively, efficiently, and fairly to support the welfare of the community. This article aims to analyze spatial planning policies at the local government level, covering aspects of planning, implementation, and challenges faced in their implementation. The research method used is library research by examining academic literature, laws and regulations, and regional planning documents. The results of the study show that although local governments already have legal instruments such as RTRW (Regional Spatial Plan) and RDTR (Detailed Spatial Plan), challenges such as weak coordination between sectors, limited resources, and land conflicts of interest are still the main obstacles. Policy synergy, institutional capacity building, and the use of spatial technology are needed to support the effectiveness of regional spatial planning.